2015
DOI: 10.1016/j.molcel.2015.01.035
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitous yybP-ykoY Riboswitch Is a Manganese-Responsive Regulatory Element

Abstract: SUMMARY The highly-structured, cis-encoded RNA elements known as riboswitches modify gene expression upon binding a wide range of molecules. The yybP-ykoY motif was one of the most broadly distributed and numerous bacterial riboswitch whose cognate ligand was unknown. Using a combination of in vivo reporter and in vitro expression assays, equilibrium dialysis and northern analysis, we show that the yybP-ykoY motif responds directly to manganese ions in both Escherichia coli and Bacillus subtilis. The identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
144
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(160 citation statements)
references
References 44 publications
10
144
0
Order By: Relevance
“…Furthermore, each discovery links the riboswitch ligand to the protein products of the genes under regulation. Recent riboswitch findings have exposed unique facets of biology, such as the widespread molecular mechanisms that confer fluoride (5) or guanidine (6) resistance, that maintain metal ion homeostasis (7)(8)(9), and that control important bacterial processes such as sporulation, biofilm formation, and chemotaxis (10)(11)(12)(13)(14). Thus, the identification of additional riboswitch classes promises to offer insights into otherwise hidden biological processes and their regulation.…”
mentioning
confidence: 99%
“…Furthermore, each discovery links the riboswitch ligand to the protein products of the genes under regulation. Recent riboswitch findings have exposed unique facets of biology, such as the widespread molecular mechanisms that confer fluoride (5) or guanidine (6) resistance, that maintain metal ion homeostasis (7)(8)(9), and that control important bacterial processes such as sporulation, biofilm formation, and chemotaxis (10)(11)(12)(13)(14). Thus, the identification of additional riboswitch classes promises to offer insights into otherwise hidden biological processes and their regulation.…”
mentioning
confidence: 99%
“…One of the longest-unresolved orphan riboswitch candidates was the yybP motif RNA . After many years of uncertainty (Meyer et al 2011), both genetic (Dambach et al 2015) and structural (Price et al 2015) data eventually confirmed the hypothesis (Waters et al 2011) that members of this orphan riboswitch candidate naturally respond to Mn 2+ ions. A total of 4383 representatives of this riboswitch class have been identified in species from 18 divisions of bacteria, indicating that this riboswitch and its natural ligand are broadly important for bacteria.…”
Section: Five Distinct Riboswitch Classes Sense Atomic Ionsmentioning
confidence: 68%
“…Although mneA was regulated in response to manganese, V. cholerae lacks an identifiable homolog of MntR, a transcriptional regulator. Interestingly, a yybP/ykoY manganese-responsive riboswitch is present upstream of E. coli mntP (36,37), and a very similar structural element is also present upstream of V. cholerae mneA. In E. coli, this riboswitch binds manganese to induce a conformational change in the mRNA that exposes the start codon, leading to increased translation.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, this riboswitch binds manganese to induce a conformational change in the mRNA that exposes the start codon, leading to increased translation. Additionally, elements upstream of the E. coli riboswitch contribute to increased transcription in the presence of manganese (37). This suggests that there are independent transcriptional and translational effects of manganese on the expression of mntP.…”
Section: Discussionmentioning
confidence: 99%